Association of neuropsychiatric syndromes with global clinical deterioration in Alzheimer's disease patients. (17th December 2015) - Stella, Florindo; Laks, Jerson; Govone, José Sílvio; de Medeiros, Kate; Forlenza, Orestes Vicente
ABSTRACT: Background: Data on the relationship between behavioral disturbances in Alzheimer's disease (AD) and global clinical deterioration is still controversial. The purpose of this study was to explore potential correlations of neuropsychiatric syndromes with global clinical deterioration in patients with AD, with particular consideration on severity levels of dementia. Methods: AD patients ( n = 156) aged 76.7 years from Brazilian clinical centers were assessed to diagnose the five neuropsychiatric syndromes measured by the Neuropsychiatric Inventory-Clinician rating scale (NPI-C): psychosis, agitation, affective, apathy, and sleep. These syndromes were then analyzed for their correlation with the Global Deterioration Scale (GDS). To analyze the association of neuropsychiatric syndromes with the GDS, considering the total sample and patients grouped by dementia severity levels, we applied the coefficient of multiple correlation (Ryy), adjusted multiple linear regression, and the coefficient of determination (R 2 yx). We tested the significance of correlation coefficients using the Student t-test for simple correlations (a single independent variable) and analysis of variance (ANOVA) for multiple correlations. ANOVA was also used to compare means of demographic and some clinical variables at different levels of dementia. Results: For the total sample, apathy and agitation syndromes were most strongly correlated (0.74; 0.72, respectively) with clinical deterioration according to the GDS, followed by psychosis (0.59), affective (0.45), and sleep syndromes (0.34). Agitation significantly correlated with mild and moderate dementia (CDR 1: 0.45; and CDR 2: 0.69, respectively). At CDR 2, agitation and affective syndromes were most strongly correlated (0.69; 0.59, respectively) with clinical deterioration while at CDR 3, the apathy syndrome was most strongly correlated with clinical deterioration (0.52). Conclusions: Agitation, apathy, and affective disorders were the syndromes most strongly correlated with global deterioration in AD patients, becoming more evident at severe stages of dementia.